Dyslipidemia Is Associated With Tunneled‐Cuffed Catheter‐Related Central Venous Thrombosis in Hemodialysis Patients: A Retrospective, Multicenter Study. Issue 8 (2nd May 2013) - Cheng, Yuan; Cui, Tianlei; Fu, Ping; Liu, Fang; Zhou, Li
Abstract The aim of this study was to explore the risk factors of tunneled‐cuffed catheter (TCC)‐related central venous thrombosis (CVT) for the maintenance of hemodialysis patients. In this study, 285 patients on maintenance hemodialysis were enrolled who had received their first TCC in the right jugular vein. Patients were divided into CVT and control groups according to the diagnosis of TCC‐related CVT 6 months after catheterization. Patients with CVT had a higher prevalence of dyslipidemia (50.74 vs. 26.85%, respectively) and low protein store compared with the control group. After adjusting for confounders, serum triglycerides (OR: 3.632; 95% CI: 2.105–6.267), non‐HDL cholesterol (OR: 1.463; 95% CI:1.067–2.007), and low‐density lipoprotein/high‐density lipoprotein (LDL/HDL) cholesterol ratio (OR: 2.904; 95% CI: 1.797–4.692) were positively correlated with TCC‐related CVT, while serum HDL cholesterol (OR: 0.097; 95% CI: 0.037–0.257) and serum albumin (OR: 0.922; 95% CI: 0.864–0.985) were negatively correlated. Dyslipidemia and low serum albumin levels were significantly associated with TCC‐related CVT in hemodialysis patients.